Insured clients out-of-pocket payments for health care under the national health insurance scheme in Ghana - Patricia Akweongo; Moses Aikins; Kaspar Wyss; Paola Salari; Fabrizio Tediosi (BMC, 2021)
Abstract Background In 2003, Ghana implemented a National Health Insurance Scheme (NHIS) designed to promote universal health coverage and equitable access to health care. The scheme has largely been successful, yet it is confronted with many challenges threatening its sustainability. Out-of-pocket payments (OOP) by insured clients is one of such challenges of the scheme. This study sought to examine the types of services OOP charges are made for by insured clients and how much insured clients pay out-of-pocket. Methods This was a descriptive cross-sectional health facility survey. A total of 2066 respondents were interviewed using structured questionnaires at the point of health care exit in the Ashanti, Northern and Central regions of Ghana. Health facilities of different levels were selected from 3 districts in each of the three regions. Data were collected between April and June 2018. Using Epidata and STATA Version 13.1 data analyses were done using multiple logistic regression and simple descriptive statistics and the results presented as proportions and means. Results Of all the survey respondents 49.7% reported paying out-of-pocket for out-patient care while 46.9% of the insured clients paid out-of-pocket. Forty-two percent of the insured poorest quintile also paid out-of-pocket. Insured clients paid for consultation (75%) and drugs (63.2%) while 34.9% purchased drugs outside the health facility they visited. The unavailability of drugs (67.9%) and drugs not covered by the NHIS (20.8%) at the health facility led to out-of-pocket payments. On average, patients paid GHS33.00 (USD6.6) out-of-pocket. Compared to the Ashanti region, patients living in the Northern region were 74% less at odds to pay out-of-pocket for health care. Conclusion and recommendation Insured clients of Ghana's NHIS seeking health care in accredited health facilities make out-of-pocket payments for consultation and drugs that are covered by the scheme. The out-of-pocket payments are largely attributed to unavailability of drugs at the facilities while the consultation fees are charged to meet the administrative costs of services. These charges occur in disadvantaged regions and in all health facilities. The high reliance on out-of-pocket payments can impede Ghana's progress towards achieving Universal Health Coverage and the Sustainable Development Goal 3, seeking to end poverty and reduce inequalities. In order to build trust and confidence in the NHIS there is the need to eliminate out-of-pocket payments for consultation and medicines by insured clients.